Statics and dynamics of a self-bound dipolar matter-wave droplet - Adhikari, S. K. [UNESP] (IOP Publishing, 2017)
We study the statics and dynamics of a stable, mobile, self-bound three-dimensional dipolar matter-wave droplet created in the presence of a tiny repulsive three-body interaction. In frontal collision with an impact parameter and in angular collision at large velocities along all directions two droplets behave like quantum solitons. Such a collision is found to be quasi elastic and the droplets emerge undeformed after collision without any change of velocity. However, in a collision at small velocities the axisymmeric dipolar interaction plays a significant role and the collision dynamics is sensitive to the direction of motion. For an encounter along the z direction at small velocities, two droplets, polarized along the z direction, coalesce to form a larger droplet - a droplet molecule. For an encounter along the x direction at small velocities, the same droplets stay apart and never meet each other due to the dipolar repulsion. The present study is based on an analytic variational approximation and a numerical solution of the mean-field Gross-Pitaevskii equation using the parameters of 52Cr atoms.
Keywords: Bose-Einstein condensate; dipolar atoms; Gross-Pitaevskii equation; soliton